2021
DOI: 10.1590/1980-265x-tce-2019-0352
|View full text |Cite
|
Sign up to set email alerts
|

Family Learning Demands About Post-Natal Newborn Care

Abstract: Objective to analyze the learning demands of puerperal women and their families about postnatal newborn care based on their knowledge and practices. Method this is a qualitative research developed through the Dynamis of Concrete of the Sensitive Creative Method, with 19 puerperal women and families of low-risk newborns, in a municipal hospital in Rio das Ostras, Rio de Janeiro, Brazil, from March to June 2019. Data were submitted to lexicographic analysis using the software IRaMuTeQ. Results different fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
1
7
0
6
Order By: Relevance
“…Regarding hygiene care, mothers may fear breaking a limb of the baby or injuring the baby while cleaning the umbilical stump ( 38 ) . A study conducted in Brazil, published in 2020 with the participation of 247 postpartum women aged between 20 and 34, revealed that 57.6% felt insecure about holding the baby due to its size.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hygiene care, mothers may fear breaking a limb of the baby or injuring the baby while cleaning the umbilical stump ( 38 ) . A study conducted in Brazil, published in 2020 with the participation of 247 postpartum women aged between 20 and 34, revealed that 57.6% felt insecure about holding the baby due to its size.…”
Section: Discussionmentioning
confidence: 99%
“…Por ocasião da alta hospitalar, os cuidados com a higiene e a nutrição do recém-nascido são frequentemente alvo de dúvidas e insegurança por parte das famílias. Esses cuidados foram analisados por Santos, Góes, Ledo et al (8) em um estudo que levantou as demandas de aprendizagem de puérperas e familiares sobre cuidados pós-natais de recém-nascidos. Os autores observaram que, de forma equivocada, as famílias realizavam algumas práticas atreladas à herança cultural, contrariando as recomendações científicas e podendo colocar em risco a saúde do recém-nascido.…”
Section: Introductionunclassified
“…Nesse contexto, o uso de tecnologias educacionais em saúde vem ganhando um considerável espaço no que se refere à educação em saúde da população, devido ao seu potencial de estimular o empoderamento individual e coletivo através de informações e conhecimento pertinentes ao tema. Podem ser benéfica aos cuidadores, com instruções que poderão melhorar o fortalecimento de vínculo afetivo e diminuir a insegurança diante do cuidado do prematuro (8)(9)(10) .…”
Section: Introductionunclassified
“…At the time of hospital discharge, care with the hygiene and nutrition of newborns is often the subject of doubts and insecurity by families. This care was analyzed by Santos, Góes, Ledo et al ( 8 ) in a study that raised the learning demands of puerperal women and their families about postnatal care for newborns. The authors observed that, mistakenly, families performed some practices linked to cultural heritage, contrary to scientific recommendations and may endanger newborns’ health.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the use of educational technologies in health has been gaining considerable space in terms of health education for the population, due to its potential to encourage individual and collective empowerment through information and knowledge relevant to the topic. They can be beneficial to caregivers, with instructions that can improve the strengthening of affective bonding and reduce insecurity in premature baby care ( 8 - 10 ) .…”
Section: Introductionmentioning
confidence: 99%